2018
DOI: 10.1097/brs.0000000000002623
|View full text |Cite
|
Sign up to set email alerts
|

Sex Specific Sacroiliac Joint Biomechanics During Standing Upright

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 22 publications
2
55
0
4
Order By: Relevance
“…SIJ pain is a common disease that affects 90% of adults throughout their lives [ 2 ]. Manipulations have a good effect on SIJ pain with no specific cause.…”
Section: Discussionmentioning
confidence: 99%
“…SIJ pain is a common disease that affects 90% of adults throughout their lives [ 2 ]. Manipulations have a good effect on SIJ pain with no specific cause.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior ligaments (5) Posterior superior iliac spine to sacral tubercles Sacral extension Long ligament Short ligament Sacrotuberous (4) Posterior superior iliac spine and sacrum to ischial tuberosity Sacral flexion Sacrospinous (3) Apex of the sacrum to ischial spine Sacral flexion Anterior ligament (6) Crosses ventral and caudal aspect of SIJ Sacral flexion, axial rotation Interosseous (8) Between sacrum and ilium dorsal to SIJ Sacral flexion, axial rotation Iliolumbar (…”
Section: Location Primary Restraintmentioning
confidence: 99%
“…4 These sex differences also reflect in the biomechanics of the joint: the female SIJ has higher mobility, and more stresses, loads, and pelvisligament strains, compared to the male SIJ. 5 Recent studies have reported a higher prevalence of LBP due to the SIJ, with some reports having estimated that the SIJ is the actual source of pain in 15% to 30% of cases. [6][7][8] From an anatomical perspective, pathologic changes and injuries specific to different SIJ structures can result in SIJ pain.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the biomechanics of the SIJ after spinal or SIJ fusion using a computational approach. [45][46][47] Mao et al 48 investigated the effect of lumbar lordosis alteration on sacrum angular displacement after lumbosacral fusion using finite element analysis. Decreasing and increasing lumbar lordosis resulted in increased sacrum angular motion.…”
Section: In Silico Studiesmentioning
confidence: 99%